2019
DOI: 10.1007/s11010-019-03537-4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired l-arginine metabolism marks endothelial dysfunction in CD73-deficient mice

Abstract: Changes in the ecto-5′-nucleotidase activity—an extracellular nucleotide catabolic enzyme may lead to the inflammation and endothelial dysfunction. We investigated the effect of CD73 deletion on the endothelial function and l -arginine metabolism in various age groups of mice. 1-,3-,6-, and 12-month-old, male C57BL/6 J wild type (WT) and C57BL/6 J CD73−/− (CD73−/−) mice were used. Blood samples were used for the analysis of adenine nucleotide concentrations. Serum samples were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
4
12
0
Order By: Relevance
“…CD73 knock-out results in a decrease in basal coronary flow, increased fibrosis, and greater cardiomyocyte hypertrophy after a transverse aortic constriction procedure [ 42 , 43 ]. Moreover, our earlier studies indicated that the deletion of CD73 leads to aortic valve and endothelial dysfunction [ 44 , 45 ]. It is well known that deterioration in heart and vascular function may result in changes in cardiac metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…CD73 knock-out results in a decrease in basal coronary flow, increased fibrosis, and greater cardiomyocyte hypertrophy after a transverse aortic constriction procedure [ 42 , 43 ]. Moreover, our earlier studies indicated that the deletion of CD73 leads to aortic valve and endothelial dysfunction [ 44 , 45 ]. It is well known that deterioration in heart and vascular function may result in changes in cardiac metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was brought to pH 6.0–6.5 using 3 M K3PO4 and analyzed with HPLC according to the method described earlier. [ 45 , 46 ] ADA1 activity was calculated from the difference between tADA and ADA2 activities.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was brought to pH 6.0-6.5 using 3 M K3PO4 and analyzed with HPLC according to the method described earlier. [45,46] ADA1 activity was calculated from the difference between tADA and ADA2 activities. Concentration of soluble CD163 and galectin-3 in human plasma were measured using enzyme-linked immunosorbent assay kits according to the manufacturer's protocols.…”
Section: Determination Of the Plasma Activities Of Ada Iso-enzymesmentioning
confidence: 99%
“…To the best of the authors' knowledge, the direct upstream and downstream relationship between apoM and IL-10 has yet to be elucidated, thus, in the present study, the expression levels of IL-10 in apoM −/− mice were determined and further analyses were performed to confirm the interaction between IL-10 and apoM. Serum ICAM-1 and VCAM-1 are generally detected by enzyme-linked immunosorbent assay ( 36 , 37 ), but in the present study, they were not detected using western blotting and enzyme-linked immunosorbent assay, probably because their expression levels were too low.…”
Section: Discussionmentioning
confidence: 98%